Profitability and resource use efficiency of potato cultivation in Munshiganj district of Bangladesh (SAARC Journal of Agriculture, 2018)
Potato is the third largest food crop in Bangladesh by tonnage of production. Its acreage and production are also increasing in day after day. This study was accomplished to examine the profitability and resource use efficiency of potato cultivation in five upazilas of Munshiganj district of Bangladesh. A total of 52 farmers were selected randomly from the study area. Data were collected through farm survey by using a suitable pre-tested questionnaire in February-March, 2016. Profitability analysis, Cobb-Douglas production function, MVP, MFC and Farm Budgeting model were used to analyze the objectives. Average gross return, gross margin and net return were found Tk. 3,47,200, Tk. 1,47,125 and Tk. 1,17,300, respectively. Benefit-cost ratio was found 1.51 and 1.74 on full cost and variable cost basis, respectively. The key production factors, i.e. human labour, land preparation, seed, fertilizer, insecticides and irrigations had significant effect on gross return of potato. Resource use efficiency analysis revealed that farmers were not efficient in using resources in potato cultivation. Human labor, land preparation, insecticide and irrigation were under-utilized and therefore increasing use of those resources could maximize the profitability. Seed and fertilizer constituted major parts of the cost of production hence optimum use of those resources could also enhance the profitability and resource use efficiency of potato cultivation in Munshiganj district.SAARC J. Agri., 15(2): 193-206 (2017)